Subduction/obduction rate in the North Pacific diagnosed by an eddy-resolving model - 刘玲玲 黄瑞新 王凡 (Chinese journal of oceanology and limnology, 2016)
Ventilation in the North Pacifi c is examined using data from the eddy-resolving 1/12° global HYbrid Coordinate Ocean Model（HYCOM） and Quik SCAT wind stress data. For the period January 2004 to December 2006 and area 20°–40°N, the total annual subduction rate is estimated at 79 Sv, and the obduction rate 41 Sv. Resolving the small-scale and high-frequency components of the eddy fi eld can increase the subduction rate by 42 Sv, and obduction by 31 Sv. Lateral induction is the dominant contributor to enhancement of subduction/obduction, and temporal change of mixed layer depth has a secondary role. Further analysis indicates that the high-frequency components of the eddy fi eld, especially those with timescale shorter than 10 days, are the most critical factor enhancing subduction/obduction.